2017
DOI: 10.1371/journal.pone.0173564
|View full text |Cite
|
Sign up to set email alerts
|

Green tea proanthocyanidins cause impairment of hormone-regulated larval development and reproductive fitness via repression of juvenile hormone acid methyltransferase, insulin-like peptide and cytochrome P450 genes in Anopheles gambiae sensu stricto

Abstract: Successful optimization of plant-derived compounds into control of nuisance insects would benefit from scientifically validated targets. However, the close association between the genotypic responses and physiological toxicity effects mediated by these compounds remains underexplored. In this study, we evaluated the sublethal dose effects of proanthocyanidins (PAs) sourced from green tea (Camellia sinensis) on life history traits of Anopheles gambiae (sensu stricto) mosquitoes with an aim to unravel the probab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 84 publications
3
7
0
Order By: Relevance
“…gambiae, F (5,24) = 105.5, p < 0.001; Ae. aegypti, F (5,24) = 314.4, p < 0.001) but slightly higher doses were required to match the activity of neem oil that was included as positive control. However, the variation in susceptibility to ZCE toxicity was insigni cant (F (1,48) = 0.836, p = 0.365).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…gambiae, F (5,24) = 105.5, p < 0.001; Ae. aegypti, F (5,24) = 314.4, p < 0.001) but slightly higher doses were required to match the activity of neem oil that was included as positive control. However, the variation in susceptibility to ZCE toxicity was insigni cant (F (1,48) = 0.836, p = 0.365).…”
Section: Resultsmentioning
confidence: 99%
“…aegypti obtained from a mosquito culture maintained at the International Centre of Insect Physiology and Ecology (icipe), Nairobi. The insects were maintained as previously described [5] at a density of 200 larvae per 1 L of dechlorinated water under controlled insectarium conditions: temperature 30 ± 2˚C, 60-80% relative humidity (RH), and 12-h light/dark cycles.…”
Section: Experimental Procedures Mosquito Larvaementioning
confidence: 99%
See 1 more Smart Citation
“…Due to the challenges associated with the use of synthetic chemicals, the use of eco-friendly and conveniently accessible plant-based alternatives has recently been proposed as a replacement [ 39 ]. Secondary metabolites found in natural products derived from plant extracts have already been shown to induce stress, alter larval development, and delay adult emergence [ 18 , 24 ]. However, there is still a lack of understanding of the toxicity mechanisms of these plant extracts, particularly at the molecular level, which has limited their potential for absolute exploration as ecofriendly plant-based alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…tenuiflorum had a moderate larvicidal and adulticidal effect on Culex gelidus and Culex quinquefasciatus . Other studies have found that plant extracts cause toxicity by extending larval development, reducing pupation and subsequent adult emergence rates, and decreasing egg output [ 18 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%